Enterovesical Fistula Secondary to Transitional Cell Carcinoma of the Bladder - Bugeja, Mark; Mizzi, Christine; Ellul, Ernest; Bugeja, Simon; Mattocks, Stephen (The Surgery Journal, 2018)
Although fistulae between the urinary bladder and the gastrointestinal tract are not uncommon, those caused by carcinoma of the urinary bladder are rare. This report describes the case of an 85 years old male who was diagnosed with a mass involving the small bowel and the urinary bladder during the course of investigation for recurrent urinary tract infections. At laparotomy, the presence of an enterovesical fistula involving the ileum and bladder was confirmed. Histopathological examination of the resected mass showed poorly differentiated urothelial carcinoma. No early postoperative complications were encountered and postoperative cystography showed healing of the bladder without evidence of leakage. Due to the patient's age and comorbidities, no further oncological treatment was offered. Three months later the patient was readmitted to hospital with a severe pneumonia to which he succumbed.
Keywords: Enterovesical fistual; bladder cancer; transitional cell carcinoma